Philosophy of Sports: Analyzing Sports Effects for Leadership Excellence - Lenka Purnima; Behura Ajit Kumar (Sciendo, 2023)
Leadership effectiveness is one of the significant concerns in the business world. While attaining goals, leaders offer direction, encouragement, and inspiration. They aid in creating a vision and uniting people behind a common goal. The literature on leadership has shown that leaders are less effective, affecting organizations, the environment, and society. This ineffectiveness is believed to be due to their rigidity, arrogance, narcissism, and ill-being. The research on leadership has shown that, among other factors, stress is one of the leading causes of this inefficiency, affecting leaders' well-being, attitude, relationships, and organizational productivity. As a result, leaders have poor awareness of how their environment is evolving. For that reason, stress management and a leader's well-being (mental and physical fitness) become the primary concern for business organizations. Leaders are the frontrunner of organizations, leading organizational objectives such as profit maximization, continuous improvement, employee management, and stakeholder satisfaction. In order to manage the corporate goal and workplace stress, they must ensure their well-being (mental and physical fitness). This paper proposes sports to enhance leaders' well-being and team-building 'we' attitudes, which help leaders to improve the organizational productivity. This paper employs content analysis methodology to justify how sports enhance leadership effectiveness. The time has come to understand the philosophy of sports, which has several benefits that guide practitioners to maintain a balance in their professional and personal life. This paper highlights sport as a vehicle for social change and personal development in leadership effectiveness.